THE IMPACT OF INFORMATION INTEGRATION IN THE SUPPLY CHAIN ON FINANCIAL PERFORMANCE - Firdaus Alamsjah; Ahmad Seiichi Ramadhan; Andre Kusuma (Journal of Management and Business, 2012)
Companies in Indonesia are still struggling to improve their intra- and inter-firm integration, and are still in the early stages of such integration. Therefore, this study is to measure and confirm the relation of horizontal information integration within a company's cross functional integration to vertical information integration of the company with their customers and suppliers, and how that affects customer satisfaction and financial performance. We used structural equation modeling (SEM) to investigate supplier and customer integration strategies using a sample of 90 manufacturing, distribution, and retail companies in Indonesia. The respondents from each company were limited to senior managers with functional areas of expertise and responsibility. The research was conducted through a survey questionnaire. The results of the study show 1) a positive direct relationship between integrated information and customer satisfaction, 2) a positive relationship between customer satisfaction and financial performance, and 3) a positive relationship from integrated information through to financial performance. The holistic implementation of information integration strategies in other developing countries can help companies to excel and gain measurable financial performances